Anchored in Justice: Yorùbá Philosophy and the Politics of a Diverse State - Segun Gbadegesin (Yoruba Studies Review, 2021)
As a major ethnic nationality in the multinational state cobbled together and christened by Lord Frederick Lugard, the Yoruba have been an integral part of the politics of the Nigerian diverse state since 1914. From the vicissitudes of the politics of nationalist struggles against colonial imposition to the politics of independence and nation-building, the core traditional values and philosophical outlook of each of the ethnic nationalities are discernible in their approaches to the issues that confront the new state. In this paper, I identify the core traditional values of the Yoruba nationality. I focus specifically on the Yoruba fascination with justice as a guiding principle as they relate to other nationalities in dealing with the issues that confront the new state. I argue that this fascination is not an arbitrary recourse in the politics of the new state. Rather, obsession with justice has been a defining feature of intra-Yoruba dealings from precolonial times to the present. To illustrate, I recount a few historical and mythical examples from the radical and unconventional social critics, Kọrú Ọjà, Ọpálábà and Aróhánrán of the Old Ọyọ Empire, to the historical Àare ̣ Kúrunmí of Ìjàyè. Finally, I highlight a few episodes in the political development of Nigeria and the role that the Yoruba obsession with justice has played in the political journey of the country.